An alternative technique for investigating fluid flow around the hand during front crawl - Udeshi, A.; Halkon, B.; Coupland, J. (Procedia Engineering, 2013)
This paper presents the novel application of a technique for measuring flow around the hand during a simulated swim stroke with a view to enable a better understanding of propulsion generation in swimming. The technique relies on the instantaneous, non-intrusive, volumetric measurement of 3D velocity fields using a commercially available optical measurement system. A hand and forearm model was towed through a water tank to replicate the pull phase with fluid flow data being captured at regular intervals in a fixed volume through which the model moved. The measurement system included a single body, three-sensor probe for capturing pairs of images which were then processed to determine particle velocities and to characterise the flow. The results were used to investigate changes in mean velocity for six experimental cases based on three different angles of attack and two towing speeds. The results showed that the V3 V system could be used to capture velocity data around the hand and for a 45° increase in angle of attack, the velocity magnitude of the flow reduced by half, indicating the presence of lift forces.